P258 Evaluation of the feasibility of providing patients with a self-management COPD toolkit for breathlessness – 'breath-in-a-Bag'. (12th November 2019) - Clinch, L; Houchen-Wolloff, L; McSporran, K; Murphy, AC
Abstract : Introduction: Exacerbations of COPD are frightening experiences for patients; breathlessness is a key feature and many patients feel a sense of panic. Patients may seek medical help without firstly trying to manage their breathlessness themselves at home. National COPD guidelines recommend higher doses of inhaled short-acting beta-2 agonists (SABA), with the most effective way of administering via a metered dose inhaler (MDI) with a spacer device. A hand-held fan has also been shown to reduce the sensation of breathlessness. We studied the feasibility of providing patients with a breathlessness self-management toolkit. Methods: A subset of patients with COPD admitted between January-March 2019, Glenfield Hospital, Leicester were given a cloth-bag containing a salbutamol inhaler, Aerochamber Plus, hand-held fan, and a COPD self-management plan. Patients were advised to keep the pack separate from their routine treatments and somewhere easily accessible should an increase in breathlessness occur. At this time patients were encouraged to follow the written/pictorial instructions on the bag, educatingthe patient to firstly increase their bronchodilator and to use a hand-held fan. Patients were asked to complete unvalidated COPD knowledge questionnaires pre- and one-month post intervention. Results: A total of 106 out of a possible 391 (27%) COPD patients were provided with the 'Breath-in-a-Bag', (mean age 70.1, 46% male, FEV1 mean 48% predicted, FEV1 /FVC 0.47). Pre- questionnaires were returned by 71 (68%) patients, with 70 (66%) post. 46 (65%) patients knew that they could inhale up to 10 puffs of salbutamol at a time using the spacer when very breathless, however only 21 (29.6%) were aware that a hand-held fan can be used to reduce breathlessness. Knowledge improved in relation to medicine use for breathlessness (Table 1). Comments from patients included; 'I follow the instructions on the bag when breathless' 'I feel less frightened' Conclusion: The exacerbation bag was feasible to deliver to patients during an admission by COPD Nurses on the Respiratory Wards. The bag was appreciated by patients and carers. Preliminary data suggests that patient knowledge on managing breathlessness has improved following the implementation. A fully powered trial is warranted to establish the efficacy of the intervention.